1991
DOI: 10.1007/bf01958834
|View full text |Cite
|
Sign up to set email alerts
|

PRN psychotropic drug use on a psychiatric unit

Abstract: PRN psychotropic drug use is a frequent practice on psychiatric units. This study examined medical records for patient demographics and prescribing patterns of drugs. The omission of the indication and frequency of dosing for the drug were common prescribing errors. There was no significant association between diagnosis and whether a patient received PRN drugs. Anxious patients were significantly more likely to receive PRN anxiolytics whereas psychotic patients were as likely to receive PRN anxiolytics as anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 6 publications
3
37
0
Order By: Relevance
“…It is encouraging to note that documentation regarding the 'outcome of administration' was recorded in significantly more of the patient records audited in the present study, than in prior studies [1Á3, 5,7].…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…It is encouraging to note that documentation regarding the 'outcome of administration' was recorded in significantly more of the patient records audited in the present study, than in prior studies [1Á3, 5,7].…”
Section: Discussionmentioning
confidence: 68%
“…As reported in many previous studies, documentation in patient notes is either missing or incomplete [1Á5, 7,10].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Craven, Voore, and Voineskos (1987) found an association with personality disorder and use of PRN medication, while our finding was of an association between emotionally unstable but not antisocial personality disorder. The other study of PRN administration to comment upon diagnosis in relation to PRN utilisation is that of Walker (1991) which was conducted in an acute psychiatric unit and did not find an association between particular diagnoses and PRN administration. In our study, high users of PRN medication were characterised by female gender, younger age, detention on a civil section and a diagnosis of emotionally unstable personality disorder.…”
Section: Discussionmentioning
confidence: 97%
“…Forty-five percent of all patients ''Agitation stat''-intramuscularly administered antipsychotic medications (non-depot) or intramuscular lorazepam in the New York State psychiatric hospital system receiving antipsychotic medication also received at least one ''stat'' medication order in 2005, over a period of observation averaging 198 days. Other studies [20][21][22][23] have also demonstrated common use of additional as needed medications, such as a prospective study conducted in an acute university hospital setting in Switzerland [20], where 71% of the patients in a closed ward ultimately received an ''as needed'' drug over a 35-day period, including non-psychotropic medication, with almost 90% of the ''as needed'' medication being oral. In a one-month retrospective study at a state hospital in New York (that remains as one of the 17 hospitals whose data is included in this report), 23% of patients received a medication administered ''stat'' [21].…”
Section: Discussionmentioning
confidence: 96%